The Influence Of The Village Head's Leadership Style On The Performance Of Village Apparatus (Case Study of Pagar Banyu Village, Ulu Talo District, Seluma Regency - Pratama, Jovi Andesta; Islamuddin, Islamuddin (Jurnal Fokus Manajemen, 2024)
This research was conducted at the Pagar Banyu Village office, Ulu Talo Subdistrict, Seluma Regency, Bengkulu Province. It is a qualitative study with a descriptive approach, utilizing questionnaires and observations for the collection of scientific data and information. The study examines “The Influence of the Village Head’s Leadership Style on the Perfomance of Village Apparatus in Pagar Banyu Village, Ulu Talo Subdiscrit, Seluma Regerency.” The population in this study consited of 20 village apparatus and residents of Pagar Banyu Village. The sampling technique involved selecting 20 individuals, comprising village apparatus and some residents of Pagar Banyu Village. Data collection methods included observation and distribution of questionnaires to the apparatus and some local residents. Data analysis techniques employed instrument validity and reliability tests, simple linear regression analysis, as well as t-test and hypothesis testing.Based on the data analysis, it was found that the leadership style significantly influences the perfomance of Village apparatus, as evidenced by the results of simple linear regression y = 9.481 + 0.438x. the calculated t-value was greater than the critical t-value. If the leadership style of the village head is equal to 0, the perfomance of Village head has a positive and significant effect on the perfomamance of the apparatus in Pagar Banyu Village, Ulu Talo, Seluma. This implies that the hypothesis is accepted.